1998
DOI: 10.1097/00007890-199810270-00027
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil-Induced Villous Atrophy

Abstract: Mycophenolate mofetil (MMF) is a new immunosuppressant developed for the prevention and treatment of acute renal rejection after transplantation. Diarrhea is the most frequent side effect observed during treatment with MMF. Its pathogenic mechanisms remain unknown. We describe a case of severe diarrhea due to villous atrophy in a renal transplant recipient during treatment with MMF. The patient was free of symptoms before MMF. Villous atrophy disappeared a few months after MMF withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 0 publications
0
40
0
3
Order By: Relevance
“…In humans, adverse events resulting from immunosuppression with MMF involving the gastrointestinal tract 7 include nausea, vomiting, abdominal pain and diarrhoea 8 . Additional studies have provided evidence for a possible direct toxic effect on intestinal epithelial cells 9 . Recent reports on impaired anastomotic healing in experimental models 6,10 underline the fact that MMF and/or its metabolites affect the integrity of the intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, adverse events resulting from immunosuppression with MMF involving the gastrointestinal tract 7 include nausea, vomiting, abdominal pain and diarrhoea 8 . Additional studies have provided evidence for a possible direct toxic effect on intestinal epithelial cells 9 . Recent reports on impaired anastomotic healing in experimental models 6,10 underline the fact that MMF and/or its metabolites affect the integrity of the intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…One of these patients was re-endoscoped at 6 months with normal findings. Other clinical studies [4] and experimental studies in rats [5] have also demonstrated villous atrophy associated with treatment with MMF. Unfortunately, our patient declined endoscopy for which reason these findings could not be validated.…”
Section: Discussionmentioning
confidence: 90%
“…17 Around 16% to 64% of immunosuppressive therapy-related incidences of diarrhea have been previously reported through clinical trials, which were dependent on the duration of study and regimen used. 1 Recent findings in renal transplant recipients suggested that unexplained causes of severe diarrhea account for less than 20% of cases after exclusion of and treatment of infectious causes and decreases in dose immunosuppressive agents.…”
Section: Discussionmentioning
confidence: 99%